Gold-catalyzed intermolecular oxidative diyne cyclizations via 1,6-carbene transfer - Wang, Qian; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2020)
A vinyl/α-oxo carbene is generated via an α-oxo carbene formation and subsequently transferred across the second alkyne. These highly active species can react with nitriles in an intermolecular fashion to provide substituted oxazoles. This methodology goes through 1,6-carbene shift and offers a range of valuable products.